Furmonertinib plus pemetrexed in the treatment of EGFR exon 19 deletion lung adenocarcinoma: two case reports - Zhang, Yuan; Wang, Duofang; Ma, Huaxiu; Wang, Xiaojun (Frontiers in Oncology, 2026)
Epidermal growth factor receptor (EGFR) exon 19 deletion (Ex19del) is one of the most prevalent sensitizing mutations in non-small cell lung cancer (NSCLC), particularly in Asian populations. However, management after progression or suboptimal response is unclear. We describe two patients with advanced lung adenocarcinoma harboring EGFR Ex19del who received furmonertinib plus pemetrexed. Case 1 achieved partial response (PR) with substantial tumor shrinkage and a marked decline in carcinoembryonic antigen (CEA) after six cycles; disease remained stable over 19 months of follow-up. Case 2 had suboptimal benefit from first-line osimertinib but attained PR with resolution of pleural effusion after switching to the combination; subsequent computed tomography (CT) confirmed stable disease (SD). Both patients tolerated treatment without severe treatment-related adverse events. These observations suggest that furmonertinib plus pemetrexed may have antitumor activity and acceptable tolerability in EGFR Ex19del lung adenocarcinoma, and may inform personalized approaches following resistance to first-line therapy in EGFR-sensitizing NSCLC.